A universal method for simultaneous surface modification and interlayer intercalation of MXenes

By performing Lewis alkaline halide treatment on MXene, changing its surface groups and layer spacing, the problem of large volume expansion/shrinkage of lithium-ion battery anode material during charging and discharging is solved, achieving efficient storage of lithium ions and improving battery performance effect.

CN115732626BActive Publication Date: 2025-02-25SHANDONG VANADIUM MATERIAL TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210899311.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-28
Publication Date
2025-02-25
Estimated Expiration
2042-07-28

AI Technical Summary

Technical Problem

The existing lithium-ion battery anode material expands/contracts greatly during charging and discharging, limiting its application in high-performance energy storage equipment.

Method used

By using the Lewis basic halide treatment method, the MXene was surface modified and interlayer interlayer interlayers were changed to improve its electrochemical properties.

Benefits of technology

It realizes MXene's efficient storage of lithium ions, improves the energy storage rate and cycle stability of lithium ion batteries, and is suitable for high-performance energy storage equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115732626B_ABST
    Figure CN115732626B_ABST
Patent Text Reader

Abstract

The present invention proposes a universal method for simultaneously surface modifying and interlayer intercalating MXene using ions in a low-temperature eutectic molten salt, so as to realize the functionalization of MXene (two-dimensional transition metal carbonitride) based materials. The present invention comprises two parts: a two-dimensional multilayer MXene and a MXene treated with a Lewis alkali halide. The multilayer MXene is obtained by etching and peeling off the MAX phase. The surface group types of the LB‑MXene treated with a Lewis alkali halide are changed from F to Cl, Br, and I. At the same time, cations are inserted into the interlayers of the MXene to expand the interlayer spacing. The Ti3C2T x After surface modification and intercalation of Lewis base halides, MXene showed a high conductivity at 0.1 A g ‑1 The specific capacity is 229 mAh g ‑1 , than pure Ti3C2T x MXene is nearly 2 times higher. LB‑MXene can also be used in electromagnetic shielding, sensors and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention belongs to the technical field of lithium ion energy storage materials, relates to lithium ion battery electrode materials, and particularly relates to a universal method for simultaneously performing surface modification and interlayer intercalation on MXene. Background technology:

[0002] Energy storage technology has profoundly changed our lives, and the continuous pursuit of high-performance energy storage technology will continue to promote social progress. Lithium-ion batteries are a typical modern industry that originated in the laboratory and are in a leading position in the field of smart terminals and electric vehicle power sources. The negative electrode material is an important component of lithium-ion batteries and has an important influence on the electrochemical properties of lithium-ion batteries. Graphite and lithium alloy materials are the most studied initial negative electrode materials, but the kinetic limitations of lithium alloy electrodes, especially the large volume expansion / contraction during charging and discharging, hinder their application in high-performance energy storage devices. Researchers are committed to finding advanced electrode materials with high multi-performance and long cycle life. MXenes have attracted much attention due to their good mechanical flexibility, good conductivity, large specific surface area, and rich chemical active sites, and are considered to be one of the most promising lithium-ion battery pack materials.

[0003] It is worth noting that the influence of surface groups and interlayer spacing on the physical and chemical properties of MXenes is huge. For example, a larger interlayer spacing is conducive to more and faster ion transport, thus having a higher energy storage rate. + The electrode material has a higher capacity, while the fluorine-based MXene hinders the Li + The synthesis method mainly determines the interlayer spacing and surface group types of MXenes. x Controllable superconductivity can be achieved by regulating surface groups.

[0004] This application uses Lewis alkaline halide MXenes that simultaneously change the surface groups and expand the interlayer spacing. Lewis alkaline AlBr3 / NaBr / KBr and AlI3 / NaI / KI eutectic molten salts with melting points of about 90°C and 155°C are used to treat MXene (the treated sample is recorded as LB-MXene). Figure 1 As can be seen from the figure, due to the desolvation of cations (Na + and K + ) are inserted into the MXene interlayer, resulting in an increase in the interlayer spacing of the MXene, and the F groups are substituted by reacting with the desolvated Br and I anions. Interestingly, this method is generally applicable to various MXenes, including mono / bimetallic MXenes, 21-phase, 32-phase, and 43-phase MXenes, as well as MXenes synthesized by different methods, thus demonstrating that LB-Ti3C2Tx Potential application prospects as lithium ion storage electrode materials. Summary of the invention:

[0005] Here, we propose a method to simultaneously design the interlayer spacing and surface modification of various MXenes by Lewis base halide treatment. Thanks to the abundant extractable cations and halogen anions in the molten Lewis base halide, the efficient intercalation of the extractable cations on MXenes increases the interlayer spacing and substitution occurs between the extractable halogen anions and -F groups.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for simultaneously performing surface modification and interlayer intercalation on MXene using ions in a eutectic molten salt is used to achieve functionalization of MXene-based materials. The invention comprises two parts: a two-dimensional multilayer MXene and a MXene treated with a Lewis alkaline halide. The multilayer MXene is obtained by etching and peeling the MAX phase. The surface group type of the MXene treated with a Lewis halide is changed from F to (Cl, Br, I), and cations are inserted into the interlayer of the MXene.

[0008] Preferably, the multilayer MXene has an electrical conductivity of 200 S m -1 , the lateral length is 20μm.

[0009] Preferably, the MXene includes but is not limited to Ti2C, Ti3C2, Mo2C, Mo2TiC2, Mo2Ti2C3, V2C, Nb4C3 or Ta4C3.

[0010] Preferably, the LB-MXene is obtained by treating MXene with aluminum bromide, sodium bromide, potassium bromide (chloride, iodide) in a molten state. The melting point of the eutectic molten salt is low. In addition, the free anions in the molten salt can react with the groups on the surface of the MXene as nucleophiles without desolvation. At the same time, the cations are inserted into the MXene interlayer to expand the interlayer distance of the MXene.

[0011] A method for simultaneously surface modifying and interlayer intercalating MXene using a low-temperature eutectic molten salt comprises the following steps:

[0012] Step 1: MXene obtained by etching the MAX phase;

[0013] Step 2: The MXene obtained in step 1 is repeatedly centrifuged with deionized water at a speed of 3500 rpm for 5 minutes each time until the pH value of the supernatant is equal to 6, thereby obtaining multilayer MXene;

[0014] Step 3: Place the multilayer MXene obtained in step 2 in a vacuum drying oven and dry at 60°C for 12 hours to obtain a dry multilayer MXene;

[0015] Step 4: Lewis basic aluminum bromide AlBr3, sodium bromide NaBr and potassium bromide KBr are placed in a glove box and mixed in a ratio of 48.7:15.2:36.1. After heating with chloride salt and iodine salt at 230°C for several minutes, aluminum bromide, sodium bromide and potassium bromide melt into a clear liquid;

[0016] Step 5: Add the dried multilayer MXene obtained in step 3 to the molten salt liquid obtained in step 4, and heat and stir at 230 °C for 6 h to obtain LB-MXene. The desolvated cation Na in the Lewis alkaline halide + and K + Inserted into the interlayer of MXene, the interlayer distance of MXene is expanded, and the surface groups between the desolvated halogen anions and F groups are replaced by Cl, Br and I;

[0017] Step 6: Wash the LB-MXene obtained in step 3 with anhydrous ether, tetrahydrofuran and deionized water three times respectively to obtain clean multilayer LB-MXene;

[0018] Step 7: After adding water to the clean multilayer LB-MXene obtained in step 6 and ultrasonicating for 1 hour, the mixture was repeatedly centrifuged at 3500 rpm for 5 minutes, and the supernatant was collected to obtain a single-layer LB-MXene;

[0019] Step 8: The working electrode is composed of LB-MXene material acetylene black and N-methyl-2-pyrrolidone (NMP) solution and 5% PVDF in a mass ratio of 7:1.5:1.5;

[0020] Step 9: Use a scraper to evenly apply the material on the copper foil, and place the copper foil with active material in a drying oven at 50°C for 1 hour;

[0021] Step 10: Place the copper foil from step 9 in a vacuum drying oven at 60°C for 12 hours, and finally cut the copper foil into multiple pieces with a diameter of 13 mm as electrodes;

[0022] Step 11: Assemble the electrodes from step 9 into a CR2016 coin-type battery for electrochemical testing.

[0023] Preferably, the step one comprises different types of MXenes.

[0024] To synthesize Ti2C, 1 g of Ti2AlC was added into 10 mL of 10 wt.% HF and stirred at room temperature for 8 h.

[0025] To synthesize Ti3C2, 1 g of Ti3AlC2 was added to 20 mL of an etchant containing 12 mL of 9 M HCl, 2 mL of 49 wt.% HF, and 6 mL of deionized water, and then stirred at room temperature for 24 h.

[0026] To synthesize Mo2C, add 1g Mo2Ga2C to 10mL 48-50wt.% HF and stir at 55°C for 100h;

[0027] To synthesize Mo2TiC2, 1 g of Mo2TiAlC2 was added into 10 mL of 48-50 wt.% HF and stirred at 55 °C for 48 h.

[0028] To synthesize Mo2Ti2C3, 1 g Mo2Ti2AlC3 was added into 10 mL of 48-50 wt.% HF and stirred at 55 °C for 96 h;

[0029] To synthesize Nb2C, Nb2AlC was added to 10 ml of 48-50 wt.% HF and stirred at room temperature for 90 h;

[0030] To synthesize V2C, 1 g of V2AlC was added to 10 ml of 48-50 wt.% HF and stirred at room temperature for 90 h.

[0031] To synthesize Nb4C3, 1 g Nb4AlC3 was added into 10 mL of 48-50 wt.% HF and stirred at room temperature for 96 h.

[0032] To synthesize Ta4C3, 1g Ta4AlC3 was selectively etched in 48-50wt.% HF at room temperature for 72h.

[0033] The stirring speed of the above synthesis was set to 400 rpm.

[0034] To synthesize molten salt prepared Ti3C2 (MS-Ti3C2), a mixture of 1g Ti3AlC2 and 2.1g CuCl2 (in a stoichiometric molar ratio of 1:3) was mixed and ground for 10min. Then 0.6g NaCl and 0.76g KCl were added to the mixture and mixed and ground for 10min. The mixture was placed in an alumina porcelain boat, which was placed in a tube furnace under argon atmosphere. The powder mixture was heated to 700℃ with a heating gradient of 4℃min -1 The obtained multilayer MS-Ti3C2 was washed with deionized water to remove salt, and then washed with 0.1M ammonium persulfate solution.

[0035] The method for detecting the performance of lithium-ion batteries based on MXene and LB-MXene materials comprises the following steps:

[0036] Step 1: Turn on the electrochemical test equipment and control software, and wait for the equipment to start;

[0037] Step 2: Test on an automatic battery tester (LAN-2100) at room temperature with a voltage range of 0.2-3.0V;

[0038] Step 3: Perform four scans on an electrochemical workstation (Biologic, VMP3) to obtain CV curves. At the same time, electrochemical impedance spectroscopy (EIS) was performed on the same electrochemical workstation with an AC perturbation amplitude of 5 mV and a frequency range of 200 kHz-10 mHz.

[0039] The present invention has the following advantages:

[0040] 1. The ions in the molten salt are naked and can directly participate in intercalation and surface group substitution reactions without desolvation;

[0041] 2. The present invention has a -1 At a current density of 229 mAh g -1 The lithium ion storage capacity of MXene prepared by HF is almost twice that of MXene prepared by HF. -1 The battery was cycled 3,000 times at a current density of 1.500 W, and the capacity retention rate was above 95%. Therefore, it can be effectively applied to practical lithium-ion energy storage.

[0042] 3. The method of intercalating and modifying MXene with low-temperature eutectic molten salt of the present invention has a simple preparation process, low temperature and cost saving; it can be effectively used for potential applications in energy storage, optoelectronics, electromagnetic shielding and other fields. Description of the drawings:

[0043] Figure 1 It is Ti3C2T in Example 2 of the present invention. x Mechanism diagram of MXene interlayer spacing expansion (a) and mechanism diagram of surface group modification (b);

[0044] Figure 2 It is Ti3C2T in Example 2 of the present invention. x Comparison of SEM, XRD, STEM, and XPS of MXene before and after molten salt treatment;

[0045] Figure 3 It is Ti3C2T in Example 2 of the present invention. x Charge and discharge curves of MXene electrodes at different current densities;

[0046] Figure 4 It is Ti3C2T in Example 2 of the present invention. x MXene electrode at 3A g -1Cycling performance and Coulombic efficiency at current density. Specific implementation method:

[0047] The following is combined with Figure 1-4 The present invention is further described in detail with reference to the following examples, but the present invention is not limited to the examples.

[0048] Example 1

[0049] A method for simultaneously performing surface modification and interlayer intercalation on MXene using ions in a low-temperature eutectic molten salt, for achieving functionalization of MXene-based materials. The invention comprises two parts: a two-dimensional multilayer MXene and a MXene treated with a Lewis alkaline halide, characterized in that: the multilayer MXene is obtained by etching and peeling off the MAX phase, and the surface group type of the MXene treated with a Lewis halide is changed from F to (Cl, Br, I), and cations are inserted into the interlayer of the MXene.

[0050] A method for simultaneously surface modifying and interlayer intercalating MXene using ions in a low-temperature eutectic molten salt comprises the following steps:

[0051] Step 1: Add 1 g of Ti2AlC to 10 mL of 10 wt.% HF, stir at room temperature for 8 h at a stirring speed of 400 rpm to obtain Ti2C;

[0052] Step 2: The Ti2C obtained in step 1 is repeatedly centrifuged with deionized water at a speed of 3500 rpm for 5 minutes each time until the pH value of the supernatant is equal to 6, thereby obtaining multilayer Ti2C;

[0053] Step 3: Place the multilayer MXene obtained in step 2 in a vacuum drying oven and dry at 60 °C for 12 h to obtain dry multilayer Ti2C;

[0054] Step 4: Lewis basic aluminum bromide AlBr3, sodium bromide NaBr and potassium bromide KBr are placed in a glove box and mixed in a ratio of 48.7:15.2:36.1. After heating with chloride salt and iodine salt at 230°C for several minutes, aluminum bromide, sodium bromide and potassium bromide melt into a clear liquid;

[0055] Step 5: Add the dried multilayer MXene obtained in step 3 to the molten salt liquid obtained in step 4, and heat and stir at 230 °C for 6 h to obtain LB-MXene. The desolvated cation Na in the Lewis alkaline halide + and K + Inserted into the interlayer of MXene, the interlayer distance of MXene is expanded, and surface group substitution occurs between the desolvated halogen anions and the F groups;

[0056] Step 6: Wash the LB-MXene obtained in step 3 with anhydrous ether, tetrahydrofuran and deionized water three times respectively to obtain clean multilayer LB-MXene;

[0057] Step 7: After adding water to the clean multilayer LB-MXene obtained in step 6 and ultrasonicating for 1 hour, the clean multilayer LB-MXene was repeatedly centrifuged at a speed of 3500 rpm for 5 minutes, and the supernatant was collected to obtain a single layer of LB-MXene;

[0058] Step 8: The working electrode is composed of LB-MXene material acetylene black and N-methyl-2-pyrrolidone (NMP) solution and 5% PVDF in a mass ratio of 7:1.5:1.5;

[0059] Step 9: Use a scraper to evenly apply the material on the copper foil, and place the copper foil with active material in a drying oven and bake at 50°C for 1 hour;

[0060] Step 10: Place the copper foil from step 9 in a vacuum drying oven at 60°C for 12 hours, and finally cut the copper foil into multiple pieces with a diameter of 13 mm as electrodes;

[0061] Step 11: Assemble the electrodes from step 10 into a CR2016 coin-type battery for electrochemical testing.

[0062] Example 2

[0063] A method for simultaneously surface modifying and interlayering MXene using ions in a low-temperature eutectic molten salt to achieve functionalization of MXene-based materials. The invention comprises two parts: a two-dimensional multilayer MXene and a MXene treated with a Lewis alkaline halide, wherein the multilayer MXene is obtained by etching and peeling off a MAX phase, and the surface group type of the MXene treated with a Lewis halide is converted from F to (Cl, Br, I), and cations are inserted into the interlayer of the MXene.

[0064] A method for simultaneously surface modifying and interlayer intercalating MXene using ions in a low-temperature eutectic molten salt comprises the following steps:

[0065] Step 1: Add 1 g of Ti3AlC2 into 20 mL of an etchant containing 18 mL of 9 M HCl, 3 mL of 49 wt.% HF and 9 mL of deionized water, and then stir at room temperature for 24 h at a stirring speed of 400 rpm to obtain Ti3C2;

[0066] Step 2: The Ti3C2 obtained in step 1 is repeatedly centrifuged with deionized water at a speed of 3500 rpm for 5 minutes each time until the pH value of the supernatant is equal to 6, thereby obtaining multilayer Ti3C2, and the multilayer Ti3C2 is vacuum dried at 60°C for 6 hours;

[0067] Step 3: Place the multilayer MXene obtained in step 2 in a vacuum drying oven and dry at 60° C. for 12 hours to obtain a dry multilayer MXene;

[0068] Step 4: Lewis basic aluminum bromide AlBr3, sodium bromide NaBr and potassium bromide KBr are placed in a glove box and mixed in a ratio of 48.7:15.2:36.1. After heating with chloride salt and iodine salt at 230°C for several minutes, aluminum bromide, sodium bromide and potassium bromide melt into a clear liquid;

[0069] Step 5: Add the dried multilayer MXene obtained in step 3 to the molten salt liquid obtained in step 4, and heat and stir at 230 °C for 6 h to obtain LB-MXene. The desolvated cation Na in the Lewis alkaline halide + and K + Inserted into the MXene interlayer, expanding the interlayer distance of MXene, and surface group substitution occurs between the desolvated halogen anions and the F groups

[0070] Step 6: Wash the LB-MXene obtained in step 3 with anhydrous ether, tetrahydrofuran and deionized water three times respectively to obtain clean multilayer LB-MXene;

[0071] Step 7: After adding water to the clean multilayer LB-MXene obtained in step 6 and ultrasonicating for 1 hour, the mixture was repeatedly centrifuged at 3500 rpm for 5 minutes, and the supernatant was collected to obtain a single-layer LB-MXene;

[0072] Step 8: The working electrode is composed of LB-MXene material acetylene black and N-methyl-2-pyrrolidone (NMP) solution and 5% PVDF in a mass ratio of 7:1.5:1.5;

[0073] Step 9: Use a scraper to evenly apply the material on the copper foil, and place the copper foil with active material in a drying oven and bake at 50°C for 1 hour;

[0074] Step 10: Place the copper foil from step 9 in a vacuum drying oven at 60°C for 12 hours, and finally cut the copper foil into multiple pieces with a diameter of 13 mm as electrodes;

[0075] Step 11: Assemble the electrodes from step 10 into a CR2016 coin-type battery for electrochemical testing.

[0076] Example 3

[0077] A method for simultaneously surface modifying and interlayering MXene using ions in a low-temperature eutectic molten salt to achieve functionalization of MXene-based materials. The invention comprises two parts: a two-dimensional multilayer MXene and a MXene treated with a Lewis alkaline halide, wherein the multilayer MXene is obtained by etching and peeling off a MAX phase, and the surface group type of the MXene treated with a Lewis halide is converted from F to (Cl, Br, I), and cations are inserted into the interlayer of the MXene.

[0078] A method for simultaneously surface modifying and interlayer intercalating MXene using ions in a low-temperature eutectic molten salt comprises the following steps:

[0079] Step 1: Add 1 g of Mo2Ga2C to 10 mL of 48-50 wt.% HF, stir at 55°C for 100 hours at a stirring speed of 400 rpm to obtain Mo2C;

[0080] Step 2: The Mo2C obtained in step 1 is repeatedly centrifuged with deionized water at a speed of 3500 rpm for 5 minutes each time until the pH value of the supernatant is equal to 6, thereby obtaining multilayer Mo2C;

[0081] Step 3: Place the multilayer MXene obtained in step 2 in a vacuum drying oven and dry at 60° C. for 12 hours to obtain a dry multilayer MXene;

[0082] Step 4: Lewis basic aluminum bromide AlBr3, sodium bromide NaBr and potassium bromide KBr are placed in a glove box and mixed in a ratio of 48.7:15.2:36.1. After heating with chloride salt and iodine salt at 230°C for several minutes, aluminum bromide, sodium bromide and potassium bromide melt into a clear liquid;

[0083] Step 5: Add the dried multilayer MXene obtained in step 3 to the molten salt liquid obtained in step 4, and heat and stir at 230 °C for 6 h to obtain LB-MXene. The desolvated cation Na in the Lewis alkaline halide + and K + Inserted into the interlayer of MXene, the interlayer distance of MXene is expanded, and surface group substitution occurs between the desolvated halogen anions and the F groups;

[0084] Step 6: Wash the LB-MXene obtained in step 3 with anhydrous ether, tetrahydrofuran and deionized water three times respectively to obtain clean multilayer LB-MXene;

[0085] Step 7: After adding water to the clean multilayer LB-MXene obtained in step 6 and ultrasonicating for 1 hour, the mixture was repeatedly centrifuged at 3500 rpm for 5 minutes, and the supernatant was collected to obtain a single-layer LB-MXene;

[0086] Step 8: The working electrode is composed of LB-MXene material acetylene black and N-methyl-2-pyrrolidone (NMP) solution and 5% PVDF in a mass ratio of 7:1.5:1.5;

[0087] Step 9: Use a scraper to evenly apply the material on the copper foil, and place the copper foil with active material in a drying oven and bake at 50°C for 1 hour;

[0088] Step 10: Place the copper foil from step 9 in a vacuum drying oven at 60°C for 12 hours, and finally cut the copper foil into multiple pieces with a diameter of 13 mm as electrodes;

[0089] Step 11: Assemble the electrodes from step 10 into a CR2016 coin-type battery for electrochemical testing.

[0090] Example 4

[0091] A method for simultaneously surface modifying and interlayering MXene using ions in a low-temperature eutectic molten salt to achieve functionalization of MXene-based materials. The invention comprises two parts: a two-dimensional multilayer MXene and a MXene treated with a Lewis alkaline halide, wherein the multilayer MXene is obtained by etching and peeling off a MAX phase, and the surface group type of the MXene treated with a Lewis halide is converted from F to (Cl, Br, I), and cations are inserted into the interlayer of the MXene.

[0092] A method for simultaneously surface modifying and interlayer intercalating MXene using ions in a low-temperature eutectic molten salt comprises the following steps:

[0093] Step 1: 1 g of Mo2TiAlC2 was added into 10 mL of 48-50 wt.% HF, and stirred at 55°C for 48 hours at a stirring speed of 400 rpm to obtain Mo2TiC2;

[0094] Step 2: The Mo2TiC2 obtained in step 1 is repeatedly centrifuged with deionized water at a speed of 3500 rpm for 5 minutes each time until the pH value of the supernatant is equal to 6, thereby obtaining multilayer Mo2TiC2;

[0095] Step 3: Place the multilayer MXene obtained in step 2 in a vacuum drying oven and dry at 60° C. for 12 hours to obtain a dry multilayer MXene;

[0096] Step 4: Lewis basic aluminum bromide AlBr3, sodium bromide NaBr and potassium bromide KBr are placed in a glove box and mixed in a ratio of 48.7:15.2:36.1. After heating with chloride salt and iodine salt at 230°C for several minutes, aluminum bromide, sodium bromide and potassium bromide melt into a clear liquid;

[0097] Step 5: Add the dried multilayer MXene obtained in step 3 to the molten salt liquid obtained in step 4, and heat and stir at 230 °C for 6 h to obtain LB-MXene. The desolvated cation Na in the Lewis alkaline halide + and K + Inserted into the interlayer of MXene, the interlayer distance of MXene is expanded, and surface group substitution occurs between the desolvated halogen anions and the F groups;

[0098] Step 6: Wash the LB-MXene obtained in step 3 with anhydrous ether, tetrahydrofuran and deionized water three times respectively to obtain clean multilayer LB-MXene;

[0099] Step 7: After adding water to the clean multilayer LB-MXene obtained in step 6 and ultrasonicating for 1 hour, the mixture was repeatedly centrifuged at 3500 rpm for 5 minutes, and the supernatant was collected to obtain a single-layer LB-MXene;

[0100] Step 8: The working electrode is composed of LB-MXene material acetylene black and N-methyl-2-pyrrolidone (NMP) solution and 5% PVDF in a mass ratio of 7:1.5:1.5;

[0101] Step 9: Use a scraper to evenly apply the material on the copper foil, and place the copper foil with active material in a drying oven at 50°C for 1 hour;

[0102] Step 10: Place the copper foil from step 9 in a vacuum drying oven at 60°C for 12 hours, and finally cut the copper foil into multiple pieces with a diameter of 13 mm as electrodes;

[0103] Step 11: Assemble the electrodes from step 10 into a CR2016 coin-type battery for electrochemical testing.

[0104] Example 5

[0105] A method for simultaneously surface modifying and interlayering MXene using ions in a low-temperature eutectic molten salt to achieve functionalization of MXene-based materials. The invention comprises two parts: a two-dimensional multilayer MXene and a MXene treated with a Lewis alkaline halide, wherein the multilayer MXene is obtained by etching and peeling off a MAX phase, and the surface group type of the MXene treated with a Lewis halide is converted from F to (Cl, Br, I), and cations are inserted into the interlayer of the MXene.

[0106] A method for simultaneously surface modifying and interlayer intercalating MXene using ions in a low-temperature eutectic molten salt comprises the following steps:

[0107] Step 1: 1 g of Mo2Ti2AlC3 was added to 10 mL of 48-50 wt.% HF, stirred at 55°C for 96 hours at a stirring speed of 400 rpm to obtain Mo2Ti2C3;

[0108] Step 2: The Mo2Ti2C3 obtained in step 1 is repeatedly centrifuged with deionized water at a speed of 3500 rpm for 5 minutes each time until the pH value of the supernatant is equal to 6, thereby obtaining multilayer Mo2Ti2C3;

[0109] Step 3: Place the multilayer MXene obtained in step 2 in a vacuum drying oven and dry at 60° C. for 12 hours to obtain a dry multilayer MXene;

[0110] Step 4: Lewis basic aluminum bromide AlBr3, sodium bromide NaBr and potassium bromide KBr are placed in a glove box and mixed in a ratio of 48.7:15.2:36.1. After heating with chloride salt and iodine salt at 230°C for several minutes, aluminum bromide, sodium bromide and potassium bromide melt into a clear liquid;

[0111] Step 5: Add the dried multilayer MXene obtained in step 3 to the molten salt liquid obtained in step 4, and heat and stir at 230 °C for 6 h to obtain LB-MXene. The desolvated cation Na in the Lewis alkaline halide + and K + Inserted into the interlayer of MXene, the interlayer distance of MXene is expanded, and surface group substitution occurs between the desolvated halogen anions and the F groups;

[0112] Step 6: Wash the LB-MXene obtained in step 3 with anhydrous ether, tetrahydrofuran and deionized water three times respectively to obtain clean multilayer LB-MXene;

[0113] Step 7: After adding water to the clean multilayer LB-MXene obtained in step 6 and ultrasonicating for 1 hour, the mixture was repeatedly centrifuged at 3500 rpm for 5 minutes, and the supernatant was collected to obtain a single-layer LB-MXene;

[0114] Step 8: The working electrode is composed of LB-MXene material acetylene black and N-methyl-2-pyrrolidone (NMP) solution and 5% PVDF in a mass ratio of 7:1.5:1.5;

[0115] Step 9: Use a scraper to evenly apply the material on the copper foil, and place the copper foil with active material in a drying oven and bake at 50°C for 1 hour;

[0116] Step 10: Place the copper foil from step 9 in a vacuum drying oven at 60°C for 12 hours, and finally cut the copper foil into multiple pieces with a diameter of 13 mm as electrodes;

[0117] Step 11: Assemble the electrodes from step 10 into a CR2016 coin-type battery for electrochemical testing.

[0118] Example 6

[0119] A method for simultaneously surface modifying and interlayering MXene using ions in a low-temperature eutectic molten salt to achieve functionalization of MXene-based materials. The invention comprises two parts: a two-dimensional multilayer MXene and a MXene treated with a Lewis alkaline halide, wherein the multilayer MXene is obtained by etching and peeling off a MAX phase, and the surface group type of the MXene treated with a Lewis halide is converted from F to (Cl, Br, I), and cations are inserted into the interlayer of the MXene.

[0120] A method for simultaneously surface modifying and interlayer intercalating MXene using ions in a low-temperature eutectic molten salt comprises the following steps:

[0121] Step 1: Add Nb2AlC to 10 ml of 48-50 wt.% HF, stir at room temperature for 90 hours at a stirring speed of 400 rpm to obtain Nb2C;

[0122] Step 2: The Nb2C obtained in step 1 is repeatedly centrifuged with deionized water at a speed of 3500 rpm for 5 minutes each time until the pH value of the supernatant is equal to 6, thereby obtaining multilayer Nb2C;

[0123] Step 3: Place the multilayer MXene obtained in step 2 in a vacuum drying oven and dry at 60° C. for 12 hours to obtain a dry multilayer MXene;

[0124] Step 4: Lewis basic aluminum bromide AlBr3, sodium bromide NaBr and potassium bromide KBr are placed in a glove box and mixed in a ratio of 48.7:15.2:36.1. After heating with chloride salt and iodine salt at 230°C for several minutes, aluminum bromide, sodium bromide and potassium bromide melt into a clear liquid;

[0125] Step 5: Add the dried multilayer MXene obtained in step 3 to the molten salt liquid obtained in step 4, and heat and stir at 230 °C for 6 h to obtain LB-MXene. The desolvated cation Na in the Lewis alkaline halide + and K + Inserted into the interlayer of MXene, the interlayer distance of MXene is expanded, and surface group substitution occurs between the desolvated halogen anions and the F groups;

[0126] Step 6: Wash the LB-MXene obtained in step 3 with anhydrous ether, tetrahydrofuran and deionized water three times respectively to obtain clean multilayer LB-MXene;

[0127] Step 7: After adding water to the clean multilayer LB-MXene obtained in step 6 and ultrasonicating for 1 hour, the mixture was repeatedly centrifuged at 3500 rpm for 5 minutes, and the supernatant was collected to obtain a single-layer LB-MXene;

[0128] Step 8: The working electrode is composed of LB-MXene material acetylene black and N-methyl-2-pyrrolidone (NMP) solution and 5% PVDF in a mass ratio of 7:1.5:1.5;

[0129] Step 9: Use a scraper to evenly apply the material on the copper foil, and place the copper foil with active material in a drying oven at 50°C for 1 hour;

[0130] Step 10: Place the copper foil from step 9 in a vacuum drying oven at 60°C for 12 hours, and finally cut the copper foil into multiple pieces with a diameter of 13 mm as electrodes;

[0131] Step 11: Assemble the electrodes from step 10 into a CR2016 coin-type battery for electrochemical testing.

[0132] Example 7

[0133] A method for simultaneously surface modifying and interlayering MXene using ions in a low-temperature eutectic molten salt to achieve functionalization of MXene-based materials. The invention comprises two parts: a two-dimensional multilayer MXene and a MXene treated with a Lewis alkaline halide, wherein the multilayer MXene is obtained by etching and peeling off a MAX phase, and the surface group type of the MXene treated with a Lewis halide is converted from F to (Cl, Br, I), and cations are inserted into the interlayer of the MXene.

[0134] A method for simultaneously surface modifying and interlayer intercalating MXene using ions in a low-temperature eutectic molten salt comprises the following steps:

[0135] Step 1: Add 1 g of V2AlC to 10 ml of 48-50 wt.% HF, stir at room temperature for 90 hours at a stirring speed of 400 rpm to obtain V2C;

[0136] Step 2: The V2C obtained in step 1 is centrifuged repeatedly with deionized water at a speed of 3500 rpm for 5 minutes each time until the pH value of the supernatant is equal to 6, thereby obtaining multilayer V2C;

[0137] Step 3: Place the multilayer MXene obtained in step 2 in a vacuum drying oven and dry at 60° C. for 12 hours to obtain a dry multilayer MXene;

[0138] Step 4: Lewis basic aluminum bromide AlBr3, sodium bromide NaBr and potassium bromide KBr are placed in a glove box and mixed in a ratio of 48.7:15.2:36.1. After heating with chloride salt and iodine salt at 230°C for several minutes, aluminum bromide, sodium bromide and potassium bromide melt into a clear liquid;

[0139] Step 5: Add the dried multilayer MXene obtained in step 3 to the molten salt liquid obtained in step 4, and heat and stir at 230 °C for 6 h to obtain LB-MXene. The desolvated cation Na in the Lewis alkaline halide + and K + Inserted into the interlayer of MXene, the interlayer distance of MXene is expanded, and surface group substitution occurs between the desolvated halogen anions and the F groups;

[0140] Step 6: Wash the LB-MXene obtained in step 3 with anhydrous ether, tetrahydrofuran and deionized water three times respectively to obtain clean multilayer LB-MXene;

[0141] Step 7: After adding water to the clean multilayer LB-MXene obtained in step 6 and ultrasonicating for 1 hour, the mixture was repeatedly centrifuged at 3500 rpm for 5 minutes, and the supernatant was collected to obtain a single-layer LB-MXene;

[0142] Step 8: The working electrode is composed of LB-MXene material acetylene black and N-methyl-2-pyrrolidone (NMP) solution and 5% PVDF in a mass ratio of 7:1.5:1.5;

[0143] Step 9: Use a scraper to evenly apply the material on the copper foil, and place the copper foil with active material in a drying oven and bake at 50°C for 1 hour;

[0144] Step 10: Place the copper foil from step 9 in a vacuum drying oven at 60°C for 12 hours, and finally cut the copper foil into multiple pieces with a diameter of 13 mm as electrodes;

[0145] Step 11: Assemble the electrodes from step 10 into a CR2016 coin-type battery for electrochemical testing.

[0146] Example 8

[0147] A method for simultaneously surface modifying and interlayering MXene using ions in a low-temperature eutectic molten salt to achieve functionalization of MXene-based materials. The invention comprises two parts: a two-dimensional multilayer MXene and a MXene treated with a Lewis alkaline halide, wherein the multilayer MXene is obtained by etching and peeling off a MAX phase, and the surface group type of the MXene treated with a Lewis halide is converted from F to (Cl, Br, I), and cations are inserted into the interlayer of the MXene.

[0148] A method for simultaneously surface modifying and interlayer intercalating MXene using ions in a low-temperature eutectic molten salt comprises the following steps:

[0149] Step 1: Add 1 g of Nb4AlC3 into 10 mL of 48-50 wt.% HF, stir at room temperature for 96 hours at a stirring speed of 400 rpm to obtain Nb4C3;

[0150] Step 2: The Nb4C3 obtained in step 1 is repeatedly centrifuged with deionized water at a speed of 3500 rpm for 5 minutes each time until the pH value of the supernatant is equal to 6, thereby obtaining multilayer Nb4C3;

[0151] Step 3: Place the multilayer MXene obtained in step 2 in a vacuum drying oven and dry at 60° C. for 12 hours to obtain a dry multilayer MXene;

[0152] Step 4: Lewis basic aluminum bromide AlBr3, sodium bromide NaBr and potassium bromide KBr are placed in a glove box and mixed in a ratio of 48.7:15.2:36.1. After heating with chloride salt and iodine salt at 230°C for several minutes, aluminum bromide, sodium bromide and potassium bromide melt into a clear liquid;

[0153] Step 5: Add the dried multilayer MXene obtained in step 3 to the molten salt liquid obtained in step 4, and heat and stir at 230 °C for 6 h to obtain LB-MXene. The desolvated cation Na in the Lewis alkaline halide + and K + Inserted into the interlayer of MXene, the interlayer distance of MXene is expanded, and surface group substitution occurs between the desolvated halogen anions and the F groups;

[0154] Step 6: Wash the LB-MXene obtained in step 3 with anhydrous ether, tetrahydrofuran and deionized water three times respectively to obtain clean multilayer LB-MXene;

[0155] Step 7: After adding water to the clean multilayer LB-MXene obtained in step 6 and ultrasonicating for 1 hour, the mixture was repeatedly centrifuged at 3500 rpm for 5 minutes, and the supernatant was collected to obtain a single-layer LB-MXene;

[0156] Step 8: The working electrode is composed of LB-MXene material acetylene black and N-methyl-2-pyrrolidone (NMP) solution and 5% PVDF in a mass ratio of 7:1.5:1.5;

[0157] Step 9: Use a scraper to evenly apply the material on the copper foil, and place the copper foil with active material in a drying oven and bake at 50°C for 1 hour;

[0158] Step 10: Place the copper foil from step 9 in a vacuum drying oven at 60°C for 12 hours, and finally cut the copper foil into multiple pieces with a diameter of 13 mm as electrodes;

[0159] Step 11: Assemble the electrodes from step 10 into a CR2016 coin-type battery for electrochemical testing.

[0160] Example 9

[0161] A method for simultaneously surface modifying and interlayering MXene using ions in a low-temperature eutectic molten salt to achieve functionalization of MXene-based materials. The invention comprises two parts: a two-dimensional multilayer MXene and a MXene treated with a Lewis alkaline halide, wherein the multilayer MXene is obtained by etching and peeling off a MAX phase, and the surface group type of the MXene treated with a Lewis halide is converted from F to (Cl, Br, I), and cations are inserted into the interlayer of the MXene.

[0162] A method for simultaneously surface modifying and interlayer intercalating MXene using ions in a low-temperature eutectic molten salt comprises the following steps:

[0163] Step 1: selectively etch 1g Ta4AlC3 in 48-50wt.% HF at room temperature for 72 hours to obtain Ta4C3;

[0164] Step 2: The Ta4C3 obtained in step 1 is centrifuged repeatedly with deionized water at a speed of 3500 rpm for 5 minutes each time until the pH value of the supernatant is equal to 6, thereby obtaining multilayer Ta4C3;

[0165] Step 3: Place the multilayer MXene obtained in step 2 in a vacuum drying oven and dry at 60° C. for 12 hours to obtain a dry multilayer MXene;

[0166] Step 4: Lewis basic aluminum bromide AlBr3, sodium bromide NaBr and potassium bromide KBr are placed in a glove box and mixed in a ratio of 48.7:15.2:36.1. After heating with chloride salt and iodine salt at 230°C for several minutes, aluminum bromide, sodium bromide and potassium bromide melt into a clear liquid;

[0167] Step 5: Add the dried multilayer MXene obtained in step 3 to the molten salt liquid obtained in step 4, and heat and stir at 230 °C for 6 h to obtain LB-MXene. The desolvated cation Na in the Lewis alkaline halide + and K + Inserted into the interlayer of MXene, the interlayer distance of MXene is expanded, and surface group substitution occurs between the desolvated halogen anions and the F groups;

[0168] Step 6: Wash the LB-MXene obtained in step 5 with anhydrous ether, tetrahydrofuran and deionized water three times respectively to obtain a clean multilayer LB-MXene;

[0169] Step 7: After adding water to the clean multilayer LB-MXene obtained in step 6 and ultrasonicating for 1 hour, the mixture was repeatedly centrifuged at 3500 rpm for 5 minutes, and the supernatant was collected to obtain a single-layer LB-MXene;

[0170] Step 8: The working electrode is composed of LB-MXene material acetylene black and N-methyl-2-pyrrolidone (NMP) solution and 5% PVDF in a mass ratio of 7:1.5:1.5;

[0171] Step 9: Use a scraper to evenly apply the material on the copper foil, and place the copper foil with active material in a drying oven at 50°C for 1 hour;

[0172] Step 10: Place the copper foil from step 9 in a vacuum drying oven at 60°C for 12 hours, and finally cut the copper foil into multiple pieces with a diameter of 13 mm as electrodes;

[0173] Step 11: Assemble the electrodes from step 10 into a CR2016 coin-type battery for electrochemical testing.

[0174] Working principle:

[0175] Ions participate in the intercalation process and surface group substitution through ion exchange (cations) and nucleophilic reactions (anions), respectively. If the above two processes occur in aqueous solution, the overall activation energy increases due to the energy consumption of the necessary step of ion desolvation, which limits the reaction rate according to the Arrhenius equation. In this case, the molten salt system is particularly worthy of attention because the "naked" ions can directly participate in the reaction, which is conducive to a significant increase in the interlayer spacing and effective termination of substitution. The mechanism diagram of MXene interlayer spacing expansion and surface group modification is shown in Figure 2. Figure 1 As shown:

[0176] Due to the desolvation of cations (Na + and K + ) is inserted into the Lewis alkali halide, the interlayer spacing of MXene increases, and the -F end is connected to the desolvated Br -and I - Interestingly, this approach is generally applicable to various MXenes, including mono / bimetallic MXenes, 32-phase and 43-phase MXenes, and MXenes synthesized by different methods.

[0177] In order to explore the potential application prospects of LB-MXene, multilayer LB-Ti3C2T x (treated with Lewis base bromide) as Li + Storage electrode material. Its electrochemical performance was studied in 1M LiPF6+ / EC / DMC / EMC electrolyte with a voltage window of 0.2-3V. -1 At the scanning rate, Ti3C2T x and LB-Ti3C2T x The CV curve is as follows Figure 3 As shown, LB-Ti3C2T x The CV curve area is significantly larger than that of Ti3C2T x , indicating that the capacity is much larger. Specifically, LB-Ti3C2T x The electrode was at 0.5 mV s -1 The scan rate provided 170 mAh g -1 The specific capacity is equivalent to 218F g -1 At the same scan rate, Ti3C2T x The capacity of the electrode is even lower, at 78 mAh g -1 (99F g -1 ). When the scan rate is increased to 100 mV s -1 When Ti3C2T x The specific capacity is 14 mAh g -1 , while LB-Ti3C2T x The specific capacity is 42 mAh g -1 , is Ti3C2T x 3 times, showing that LB-Ti3C2T x In addition, F largely hinders the Li + The transport of Li + Good storage performance. LB-Ti3C2T x In 3A g -1 Cycling stability at high current density Figure 4 After 3000 cycles, its specific capacity is still 120 mAh g -1 , the capacity retention rate exceeds 95%.

[0178] The above description is only used to understand the method and core idea of ​​the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principle of the present invention, and these improvements and modifications also fall within the scope of protection of the rights of the present invention.

Claims

1. A universal method for simultaneous surface modification and interlayer intercalation of MXene, characterized in that The following steps are included: Step 1: Obtain MXene by etching the MAX phase; Step 2: The MXene obtained in step 1 is repeatedly centrifuged with deionized water at a speed of 3500 rpm for 5 minutes each time until the pH value of the supernatant is equal to 6, thereby obtaining multilayer MXene; Step 3: Place the multilayer MXene obtained in step 2 in a vacuum drying oven and dry at 60 °C for 12 h to obtain a dry multilayer MXene; Step 4: Lewis basic aluminum bromide AlBr3, sodium bromide NaBr and potassium bromide KBr are placed in a glove box and mixed in a ratio of 48.7:15.2:36.

1. After heating with chloride and iodine salts at 230 °C for several minutes, aluminum bromide, sodium bromide and potassium bromide melt into a clear liquid. Step 5: Add the dried multilayer MXene obtained in step 3 to the molten salt liquid obtained in step 4, and heat and stir at 230 °C for 6 h to obtain LB-MXene. The desolvated cation Na + and K + Inserted into the MXene interlayer, the interlayer distance of MXene is expanded, and surface group substitution with Cl, Br and I occurs between the desolvated halogen anions and the F group termination; Step 6: Wash the LB-MXene obtained in step 5 with anhydrous ether, tetrahydrofuran and deionized water three times respectively to obtain a clean multilayer LB-MXene; Step 7: After adding water to the clean multilayer LB-MXene obtained in step 6 and ultrasonicating for 1 h, repeatedly centrifuge at 3500 rpm for 5 minutes, and collect the supernatant to obtain a single-layer LB-MXene.

2. A universal method for simultaneously surface modifying and interlayer intercalating MXene according to claim 1, characterized in that: The conductivity of the multilayer Mxene obtained in step 3 is 200 S m -1 , with a lateral length of 20 μm.

3. A universal method for simultaneously surface modifying and interlayer intercalating MXene according to claim 1, characterized in that: The MXene obtained in the step 1 includes Ti2C, Ti3C2, Mo2C, Mo2TiC2, Mo2Ti2C3, V2C, Nb4C3 or Ta4C3.

Citation Information

Patent Citations

  • Positive electrode material of metal halide battery and preparation method thereof

    CN107819126A

  • Single-layer MXene nanosheets and preparation method thereof

    CN111591992A